2008
DOI: 10.1016/j.ccr.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Energy migration within the 2E state of Cr3+

Abstract: Please cite this article in press as: M. a b s t r a c tExcitation energy migration is an important phenomenon at high concentration of luminescent chromophores. In crystalline solids it results in a quenching of the intrinsic luminescence of the chromophore as the excitation energy migrates to impurity centres or other forms of trap sites. As concluded from the extensively studied systems where Cr 3+ is doped as the active chromophore into inert host lattices, energy migration in crystalline solids is usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 55 publications
1
27
0
1
Order By: Relevance
“…This result shows that the lines at 659, 699, 674, 678, 700, 706, 712, and 725 nm are phonon-sidebands of the lines R 1 and R 2 . The PLE spectra consist of two strong broad absorption bands with peak positions at around 399 and 556 nm, corresponding to spin-allowed [5,6]. Beside, a weak sharp peak at 692 nm corresponding to the transitions from the basic level 4 A 2 ( 4 F) to the lowest excited level 2 E( 2 G), is also observed.…”
Section: T = 1000mentioning
confidence: 94%
See 1 more Smart Citation
“…This result shows that the lines at 659, 699, 674, 678, 700, 706, 712, and 725 nm are phonon-sidebands of the lines R 1 and R 2 . The PLE spectra consist of two strong broad absorption bands with peak positions at around 399 and 556 nm, corresponding to spin-allowed [5,6]. Beside, a weak sharp peak at 692 nm corresponding to the transitions from the basic level 4 A 2 ( 4 F) to the lowest excited level 2 E( 2 G), is also observed.…”
Section: T = 1000mentioning
confidence: 94%
“…6 [4][5][6]. Figure 10 shows the PLE spectra of the Al 2−x Cr x O 3 samples with x = 0.005, heat-treated at 1300…”
Section: T = 1000mentioning
confidence: 99%
“…11). In addition to the well-known phonon-assisted process at elevated temperatures, two types of resonant and thus energy selective processes lead to a multi-line pattern and fast spectral diffusion, respectively, at 1.4 K. [28,29] In the complex [Ru(bpy) 2 dppz-TTF] 2+ (Fig. 12) irradiation into the metal-ligand charge transfer (MLCT) bands results in both luminescence as well as the creation of a comparatively long-lived charge separated state (τ = 2.4 µs).…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…This leads to the sequential appearance of additional sharp lines spaced by the ground-state ZFS in the FLN spectrum across the inhomogeneous line [10]. The second one is a quasi-resonant process between spectral neighbours and manifests itself by rapid spectral diffusion [9]. The third one is the well-known phonon-assisted process setting in at higher temperature.…”
Section: Introductionmentioning
confidence: 98%
“…In fact, they allow a clear distinction between different mechanisms for energy migration as depicted in Fig. 1 [9]. Fluorescence line narrowing (FLN) spectroscopy showed that at cryogenic temperatures, where phonon-assisted energy migration is negligible, two different types of resonant energy migration may take place.…”
Section: Introductionmentioning
confidence: 99%